2004
DOI: 10.1103/physrevlett.92.115504
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioStudies of Polarization and Piezoelectricity in Vinylidene Fluoride and BN-Based Polymers

Abstract: Highly piezoelectric and pyroelectric phases of boron-nitrogen-based polymers have been designed from first principles. They offer excellent electrical and structural properties, with up to 100% improvement in the piezoelectic response and an enhanced thermal stability with respect to polyvinylidene fluoride (PVDF). Since methods for their synthesis are readily available, these polymers are extremely promising for numerous technological applications, rivaling the properties of ferroelectric ceramics and supers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 33 publications
9
97
0
1
Order By: Relevance
“…As can be seen from Table I, the various models do not agree with each other, which recently motivated us to apply modern ab initio techniques to compute spontaneous polarization in ␤-PVDF. 16 Our results ͑P 3 sp = 0.178 C / m 2 ͒ clearly show that the majority of the previous models, fitted either to experiment or to a simple sum of the bond-dipole moments in an individual VDF monomer 4,7 ͑Ӎ2 D͒, underestimate the strength of the dipole-dipole interaction in this material. The polarization obtained in Ref.…”
Section: Introductionsupporting
confidence: 51%
“…As can be seen from Table I, the various models do not agree with each other, which recently motivated us to apply modern ab initio techniques to compute spontaneous polarization in ␤-PVDF. 16 Our results ͑P 3 sp = 0.178 C / m 2 ͒ clearly show that the majority of the previous models, fitted either to experiment or to a simple sum of the bond-dipole moments in an individual VDF monomer 4,7 ͑Ӎ2 D͒, underestimate the strength of the dipole-dipole interaction in this material. The polarization obtained in Ref.…”
Section: Introductionsupporting
confidence: 51%
“…In order to compare present values of the direct piezoelectric response of the monolayers with those of standard 3D piezoelectric materials, we need to define a volume and to consider, as it is generally done in these cases, a graphite-like system with interlayer distance 67 of 3.35 Å. It follows that BNG structures exhibit a direct macroscopic piezoelectricity that is about 10 times larger than that of pure α-quartz 65 or Ge-doped α-quartz, 44 5 times larger than that (0.27 C/m 2 ) of polyvinylidene fluoride and its copolymers 68 and comparable to that of bulk GaN and AlN. 66 In order to confirm that the same finite, large, piezoelectric response can be induced in graphene simply by breaking its inversion symmetry center with any in-plane defect, in the limit of low defect concentration, we introduce two other defects: holes which reduce the symmetry of graphene from D 6h to D 3h and C 2v , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The LGD intrinsic coercive field EC was found experimentally in copolymer thin films at the nanoscale [31]. Further experiments indicated that bulk polymeric ferroelectric films behave in accordance with KAI switching mechanism, while the nanoscale films reveal homogeneous LGD switching [12,13,27].…”
Section: Intrinsic Homogeneous Polarization Switchingmentioning
confidence: 72%
“…Now these LB polymer films are widely explored experimentally, using various techniques, including nanoscale characterization by atomic force microscopy (AFM) and piezoresponse force microscopy (PFM) method [4][5][6][7][8][9][10][11], and theoretically, using various computational methods [12][13][14][15][16][17][18][19][20][21]. These novel ferroelectric nano-materials are very promising for nanobiotechnology, nanobiomedicine, bio-and microelectronics, and as a prospective component of various nanocomposites and "intellectual" templates with "smart surface" properties.…”
Section: Introductionmentioning
confidence: 99%